Great by choice : uncertainty, chaos, and luck--why some thrive despite them all - Collins, James C. (James Charles), 1958- (Harper Business, 2011)
Examines nine years of research on successful businesses to help determine why some companies thrive in uncertainty while others do not, and highlights such qualities as discipline, creativity, and constancy.